Growth and production of tomato fertilized with poultry litter and swine wastewater - Alessandra Algeri; Augusto V. Luchese; Alessandro J. Sato; Laércio A. Pivetta (Revista Brasileira de Engenharia Agrícola e Ambiental)
HIGHLIGHTS Combining different sources of organic fertilizers is a viable strategy to balance the nutritional demand for tomato. Tomato can be produced without soluble mineral fertilizers. The effect of organic fertilization depends on the cultivar.